The last step to achieve barrier damage control - Baglivo, Ilaria; Colantuono, Stefania; Lumaca, Arianna; Papa, Alfredo; Gasbarrini, Antonio; Caruso, Cristiano (Frontiers in Immunology, 2024)
Heterogeneity characterises inflammatory diseases and different phenotypes and endotypes have been identified. Both innate and adaptive immunity contribute to the immunopathological mechanism of these diseases and barrier damage plays a prominent role triggering type 2 inflammation through the alarmins system, such as anti-Thymic Stromal Lymphopoietin (TSLP). Treatment with anti-TSLP monoclonal antibodies showed efficacy in severe asthma and clinical trials for other eosinophilic diseases are ongoing. The aim of this perspective review is to analyse current advances and future applications of TSLP inhibition to control barrier damage.